2021
DOI: 10.1002/batt.202000306
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Composite Anodes with Tunable Microstructures for Potassium‐Ion Batteries

Abstract: Among the post‐lithium battery technologies, potassium‐ion batteries are promising for cost‐effective large‐scale energy storage, as potash is an abundant resource. However, a major challenge is to understand the structure‐performance relationships of carbon anodes for potassium‐ion storage. In this study, we have designed a variety of carbon composite materials from 100 % graphite to 100 % soft carbon and in between, with tunable structural features to fundamentally understand the roles of different carbon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[1,62,64] Experimental XPS measurements commonly identify an oxygen content of ≈4% in HC, soft carbon, and composite carbon anodes for LIBs, NIBs, and KIBs. [66,67] Here, we consider four oxygen defects: single substitutional oxygen defect (O C ), oxygen substitutional defect and carbon vacancy (O C V C ), double oxygen substitutional defect (2O C ), and triple oxygen substitutional defect (3O C ). The O C and 2O C defects are purely substitutional in nature, whereas the O C V C defect includes a carbon vacancy.…”
Section: Oxygen Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,62,64] Experimental XPS measurements commonly identify an oxygen content of ≈4% in HC, soft carbon, and composite carbon anodes for LIBs, NIBs, and KIBs. [66,67] Here, we consider four oxygen defects: single substitutional oxygen defect (O C ), oxygen substitutional defect and carbon vacancy (O C V C ), double oxygen substitutional defect (2O C ), and triple oxygen substitutional defect (3O C ). The O C and 2O C defects are purely substitutional in nature, whereas the O C V C defect includes a carbon vacancy.…”
Section: Oxygen Defectsmentioning
confidence: 99%
“…[33,65,[76][77][78][79] For KIBs, the graphitic stacks' interlayer distances accessible to Na + and Li + storage can be inaccessible, with greater interlayer distances required. [33,61,66,80] Previously, we have studied, in isolation, basal plane defect adsorption, and intercalation in planar graphitic pores with varying interlayer distances (c) as guided by experimental HC characterization. [33,34] From these studies, we showed that metal adsorption is greatly enhanced at defect sites, [34] and that especially the sodium and potassium intercalation is heavily dependent on c, with potassium showing energetically favorable intercalation energies (i.e., negative binding energies) first at c > 3.85 Å, and sodium at c > 3.49 Å.…”
Section: Adsorption Of LI Na and K On V C N C And O C Defectsmentioning
confidence: 99%
“…Thus, a high ICE of 67.3%, reversible capacities of 280.2 mAh g −1 and a plateau‐dominated profile were obtained with the graphite‐soft carbon composite. [ 111 ] Meanwhile, compositing graphite with the hard carbon is also effective. By coating amorphous N‐doped carbon nanosheets on multilayer graphite (random orientations of the flake graphene), the resulting composite exhibits a flat discharge plateau from graphite and enhanced cyclic stability (215.7 mAh g −1 after 1000 cycles at 0.2 A g −1 ) and ICE (from uncoated graphite of 43.43% to 61.83%).…”
Section: Design Of Carbon Materials With Intercalation/capacitive Hyb...mentioning
confidence: 99%
“…[1] A greener CO 2 footprint for batteries will inevitably be a prerequisite in the near future to reach truly net-zero target commitments. [8,9] Here, new emerging battery technologies, including sodium-ion batteries, [10][11][12][13][14] potassium-ion batteries, [15,16] multivalent ion batteries, [17] and dual-ion batteries (DIBs), are regarded as more sustainable alternatives to LIBs.Among these alternatives, the advantages of DIBs (some common to the other battery chemistries) are: 1) eliminating lithium and critical elements such as nickel and cobalt thus removing the elements scarcity; 2) high working voltage and fast-charging (e.g., dual-graphite DIBs can reach a high power density of 8.66 kW kg À1 and a high energy density of 227 Wh kg À1 ); [18] and 3) sodium/potassium-based DIBs offer considerable opportunities due to the abundance of sodium reserves (2.7 wt %/28 400 mg kg À1 earth's crust; 11 000 mg L À1 seawater) and potassium reserves (2.4 wt%/26 000 mg kg À1 earth's crust; 380 mg L À1 seawater). [19] These merits allow DIBs to power small electric vehicles and large-scale stationary ("grid") energy storage.Cation-anion DIBs consist of Li-, [20] K-, [19,[21][22][23] Na-, [24] Mg-, [25] Ca-, [26] Al-, [27,28] and Zn-based [29,30] DIBs.…”
mentioning
confidence: 99%
“…[1] A greener CO 2 footprint for batteries will inevitably be a prerequisite in the near future to reach truly net-zero target commitments. [8,9] Here, new emerging battery technologies, including sodium-ion batteries, [10][11][12][13][14] potassium-ion batteries, [15,16] multivalent ion batteries, [17] and dual-ion batteries (DIBs), are regarded as more sustainable alternatives to LIBs.…”
mentioning
confidence: 99%